Film covering material for clothes and preparation method of film covering material
By using the core material of the carbon fiber, CACL2 · 6H2O, and aluminum foil in the clothing film covering material, and the combination of CU-BTC-lating soybean protein, form a microcopener structure, solving the phase-changing material The leakage and separation in the clothing cover achieves high -efficiency and moderate clothing performance.
Patent Information
- Application Number
- CN202411896060.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-24
AI Technical Summary
Phase change materials are prone to leakage and separation in clothing coating applications, affecting the use effect and life span, and it is difficult to meet the temperature control effect and basic performance requirements of clothing at the same time.
Using a core material composed of xylitol-aerogel carbon fiber, CaCl2·6H2O and aluminum foil, combined with Cu-BTC-acylated soybean protein as the shell material, a stable microcapsule structure is formed. Through the multi-level pore structure and triple molecules The force network enhances the material's mechanical strength and interfacial stability.
It significantly improves the mechanical strength and interface stability of the material, prevent the leakage and separation of phase -changing materials, and achieve excellent temperature control effects. At the same time, it meets the basic performance requirements of clothing, such as lightness, softness, and washing resistance.
Smart Images

Figure CN119352301A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of clothing coating, and in particular to a coating material for clothing and a preparation method thereof. Background Art
[0002] In the modern clothing industry, the development and application of coating materials have become an important technical means to improve the functionality of clothing. There are many types of clothing coating materials, which can be divided into four categories according to their performance characteristics and application fields.
[0003] Traditional polymer materials are the most basic and widely used, including TPU (thermoplastic polyurethane) membranes, PU (polyurethane) coatings, PTFE (polytetrafluoroethylene) membranes, and polyacrylates. These materials are widely used in outdoor sportswear and functional clothing due to their excellent waterproof and breathable properties. With the development of nanotechnology, the second type of nanomaterial-modified composite membranes came into being. By adding materials such as nano-silicon dioxide, nano-silver, and carbon nanotubes, not only the basic properties of the membrane materials are improved, but also special functions such as antibacterial, antistatic, and thermal conductivity are given, which greatly expands the application scenarios of clothing. The emergence of the third type of phase change material (PCM) composite membrane provides a new solution for the temperature regulation of clothing. This type of material mainly includes paraffin, polyols, and hydrated salts, which can store and release heat through the phase change process, thereby achieving the purpose of regulating the temperature of the human microenvironment. Especially in the field of sportswear and special protective clothing, PCM materials have shown unique advantages. The fourth type of new intelligent responsive materials represents the future development direction of clothing materials, including shape memory materials, thermosensitive hydrogels and photo / thermochromic materials. These materials can automatically adjust their performance according to environmental changes and realize intelligent functional regulation.
[0004] In terms of intelligent temperature control applications, phase change material (PCM) coating technology is the most representative. PCM materials can absorb or release latent heat through the phase change process when the temperature changes, thereby achieving the effect of regulating the temperature.
[0005] Among many applications, phase change material (PCM) coating technology has attracted much attention due to its excellent temperature regulation ability. PCM materials can absorb or release latent heat through the phase change process when the temperature changes, effectively alleviating temperature fluctuations and providing the wearer with a constant temperature and comfortable experience. However, this technology still faces many challenges in practical applications. The first problem is the packaging technology of phase change materials, which needs to maintain its good phase change properties while ensuring that the material does not leak or separate. The second is the problem of multi-functional synergy. How to achieve effective temperature regulation while maintaining the lightness, softness and washability of clothing requires in-depth research in material design and process optimization. Summary of the invention
[0006] (1) Technical issues to be resolved The purpose of the present invention is to provide a coating material for clothing to solve the problems that phase change materials are prone to leakage and separation, affecting the use effect and life, and it is difficult to simultaneously meet the temperature control effect and basic performance requirements of clothing.
[0007] (2) Technical solution To achieve the above-mentioned purpose, on the one hand, the present invention provides a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0008] Furthermore, a coating material for clothing, the core material comprises the following raw materials in parts by weight: 40-50 parts of xylitol-aerogel carbon fiber, 30-40 parts of CaCl2·6H2O, and 5-10 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 15-20 parts of Cu-BTC-acylated soybean protein.
[0009] Furthermore, the preparation method of the xylitol-aerogel carbon fiber comprises: S11. sieving xylitol through 60 mesh to obtain sieved xylitol, and vacuum drying the sieved xylitol at 60-70° C. for 8-10 hours to obtain pretreated xylitol; S12. Cut the aerogel carbon fiber into segments of 0.5 to 1 cm in length to obtain the cut aerogel carbon fiber, add the cut aerogel carbon fiber into a 3 to 5 mol / L HNO3 solution, and soak it at 70 to 80°C for 2 to 3 hours to obtain the soaked aerogel carbon fiber, continue to place the soaked aerogel carbon fiber in a 3 to 5 mol / L HNO3 solution for ultrasonic treatment for 30 to 45 minutes to obtain the ultrasonically treated aerogel carbon fiber, wash the ultrasonically treated aerogel carbon fiber with deionized water for 4 to 5 times to obtain aerogel carbon fiber washed with deionized water, wash the aerogel carbon fiber washed with deionized water with ethanol for 2 to 3 times to obtain aerogel carbon fiber washed with ethanol, and vacuum dry the ethanol-washed aerogel carbon fiber at 60 to 80°C for 12 to 24 hours to obtain the pretreated aerogel carbon fiber; S13. The pretreated xylitol is heated to 95-100° C. to obtain molten xylitol, the pretreated aerogel carbon fibers are slowly added to the molten xylitol, and mechanically stirred at 400-500 rpm for 30-40 min to obtain a mixed material, and the mixed material is ultrasonically treated at 60-70° C. for 30-40 min to obtain a mixed material after ultrasonic treatment; S14. The mixed material after ultrasound is placed in a vacuum box, evacuated to -0.08~-0.1MPa, and evacuated at 100~110°C for 2~3h to obtain a vacuum mixed material; S15. The vacuum mixed material is slowly cooled to room temperature at a cooling rate of 2 to 4 ° C / min to obtain a cooled mixed material, and the cooled mixed material is pressurized at 10 to 12 MPa using a hot press for 10 to 20 min to obtain a pressed mixed material; S16. The pressed mixed material is vacuum dried at 60-70° C. for 12-24 h to obtain xylitol-aerogel carbon fiber.
[0010] Furthermore, the preparation method of the Cu-BTC-acylated soybean protein comprises: S21. Weigh copper chloride hexahydrate and 1,3,5-benzenetricarboxylic acid, dissolve them in N,N-dimethylformamide to obtain a mixed solution, place the mixed solution in an oil bath at 70 to 80° C., and react at a constant temperature for 24 to 36 hours to obtain a mixed solution after the reaction; S22. The mixed solution after the reaction is cooled to room temperature to obtain a cooled mixed solution, the cooled mixed solution is vacuum filtered to obtain a precipitate, the precipitate is repeatedly washed with acetone for 3 to 4 times to obtain a washed precipitate, the washed precipitate is blown dry to obtain a blown-dried precipitate, and the blown-dried precipitate is vacuum dried at 60 to 70° C. for 12 to 24 hours to obtain Cu-BTC; S23. Weigh soy protein isolate and dissolve it in deionized water, and adjust the pH to 9 to 10 using 1 to 5 mol / L NaOH to obtain a soy protein isolate solution, and stir the soy protein isolate solution at room temperature for 1 to 2 hours to obtain a stirred soy protein isolate solution; S24. slowly adding acetic anhydride dropwise to the stirred soy protein isolate solution at 45-50° C. to obtain a mixed solution, stirring the mixed solution at a constant temperature for 3-4 hours to obtain a stirred mixed solution, adjusting the pH of the stirred mixed solution to 4.5-5 to obtain a pH-adjusted mixed solution, centrifuging the pH-adjusted mixed solution at 4000-6000 rpm for 15-20 minutes to obtain a precipitate, washing the precipitate with deionized water for 3-4 times to obtain a precipitate washed with deionized water, and freeze-drying the precipitate washed with deionized water for 24-36 hours to obtain an acylated soy protein; S25. dissolving the acylated soy protein in a phosphate buffer to obtain an acylated soy protein solution, ultrasonically dispersing the acylated soy protein solution for 15 to 20 minutes to obtain an acylated soy protein solution after ultrasonication, and allowing the acylated soy protein solution after ultrasonication to stand for swelling for 2 to 3 hours to obtain an acylated soy protein solution after standing; S26. Cu-BTC was added to phosphate buffer and ultrasonicated at 300-400W for 20-25min to obtain a Cu-BTC dispersion. The Cu-BTC dispersion was allowed to stand for 10-15min, and the supernatant was taken to obtain a Cu-BTC dispersion supernatant; S27. The supernatant of the Cu-BTC dispersion is added dropwise to the acylated soybean protein solution after standing at 2-3 mL / min by a constant flow pump to obtain a reaction solution, the reaction solution is ultrasonically dispersed for 30-45 min to obtain a reaction solution after ultrasonication, the reaction solution after ultrasonication is stirred at 400-500 rpm for 2-3 h to obtain a stirred reaction solution, the pH of the stirred reaction solution is adjusted to 7-8 to obtain a reaction solution with adjusted pH, the reaction solution with adjusted pH is stirred at room temperature for 1-2 h and then allowed to stand for 1-2 h to obtain a reaction solution after standing; S28. The reaction solution after standing is centrifuged at 8000-10000 rpm for 15-20 min to obtain a centrifuged reaction solution, the centrifuged reaction solution is washed with deionized water for 2-3 times and then with ethanol for 1-2 times to obtain a washed reaction solution, the washed reaction solution is vacuum dried at 60-70° C. for 8-12 h to obtain Cu-BTC-acylated soybean protein.
[0011] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a coating material for clothing, which is applied to the coating material for clothing, and comprises the following steps: S31. Grinding CaCl2·6H2O to 100-150 mesh to obtain ground CaCl2·6H2O; S32. Cut the aluminum foil into sheets of 2 to 3 mm in size to obtain cut aluminum foil, ultrasonically clean the cut aluminum foil with anhydrous ethanol for 5 to 10 minutes to obtain cleaned aluminum foil, and naturally dry the cleaned aluminum foil at room temperature to obtain pretreated aluminum foil.
[0012] S33. The ground CaCl2·6H2O and xylitol-aerogel carbon fiber were mixed in a constant temperature water bath at 25 to 29°C to obtain a first mixed material, and the pretreated aluminum foil was added to the first mixed material and gently stirred for 5 to 10 minutes to obtain a second mixed material; S34. The Cu-BTC-acylated soy protein was dissolved in anhydrous ethanol and ultrasonically treated for 10 to 15 minutes to obtain a Cu-BTC-acylated soy protein solution, and the second mixed material was added dropwise to the Cu-BTC-acylated soy protein solution at a rate of 5 to 10 mL / min to obtain a third mixed material, and the third mixed material was stirred at 200 to 300 rpm for 30 to 45 minutes to obtain a fourth mixed material; S35. Allow the fourth mixed material to stand for 2 to 3 hours to obtain the fourth mixed material after standing, centrifuge the fourth mixed material after standing at 3000 to 5000 rpm for 10 to 20 minutes to obtain the fourth mixed material after centrifugation, wash the fourth mixed material after centrifugation with deionized water for 3 to 4 times to obtain the washed fourth mixed material, and vacuum dry the washed fourth mixed material at 60 to 70° C. for 12 to 24 hours to obtain the clothing coating material.
[0013] The mechanism of action of the above raw material components is as follows: Xylitol-aerogel carbon fiber: As a composite matrix material for energy storage and heat conduction, xylitol can achieve effective storage and release of heat due to its high phase change latent heat and moderate phase change temperature range, while aerogel carbon fiber has an ultra-high specific surface area and excellent thermal conductivity, which can improve the thermal conductivity efficiency of the entire system. At the same time, its unique three-dimensional network structure can provide good physical constraints for xylitol and effectively prevent leakage problems during the phase change process.
[0014] CaCl2·6H2O: As a typical inorganic phase change material, CaCl2·6H2O has a high latent heat of phase change and a suitable phase change temperature. It can store and release heat by changing the amount of hydrate crystal water when the temperature changes. Its good thermal stability and cyclic stability enable it to maintain stable performance during repeated phase changes. At the same time, the eutectic system formed with xylitol can further improve the overall heat storage performance.
[0015] Aluminum foil: As a barrier layer in the microcapsule, aluminum foil can accelerate the transfer of heat inside the microcapsule with its excellent thermal conductivity. At the same time, its dense structure can effectively prevent the leakage of phase change materials in the molten state. In addition, aluminum foil has good chemical stability, which can prevent unnecessary chemical reactions between the core material and the external environment and extend the service life of the microcapsule.
[0016] Cu-BTC-acylated soy protein: As the shell material of microcapsules, this composite material combines the high porosity, large specific surface area and excellent thermal stability of the Cu-BTC metal organic framework with the good film-forming property and mechanical strength of the acylated soy protein. The porous structure of Cu-BTC is conducive to the rapid transfer of heat, while the acylated modified soy protein provides the necessary mechanical support and flexibility to ensure that the fabric has proper drape and comfort. The synergistic effect of the two enables the shell to protect the core material while ensuring efficient heat transfer.
[0017] (3) Beneficial effects Compared with the prior art, the present invention has the following beneficial effects: 1. Through the unique double confinement structure design, the honeycomb three-dimensional network formed by the aerogel carbon fiber is interconnected with the octahedral lattice channels of Cu-BTC to form a multi-level pore structure from nanometers to micrometers, and combined with the triple molecular force network (hydrogen bond network, coordination bond network and interface action), CaCl2·6H2O is used as an interface regulator to form a bridging network, which successfully solves the technical problem of easy leakage and separation of traditional phase change materials, and significantly improves the mechanical strength and interface stability of the material.
[0018] 2. Acylated soy protein provides the necessary mechanical support and flexibility. Its flexible peptide chain can absorb the volume stress during the phase change process. Combined with the support of the rigid skeleton of aerogel carbon fiber, it can not only prevent the deformation of the microcapsules, but also achieve stress release and buffering, ensuring that the fabric has appropriate drape and comfort, and achieving excellent temperature control effect while meeting the basic performance requirements of clothing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of xylitol-aerogel carbon fiber of Example 1 of the present invention; Figure 2 This is the SEM image of Cu-BTC-acylated soybean protein in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The test equipment and preparations of the examples described below are as follows: Electronic balance (Sartorius, Germany), electric blast constant temperature dryer (Shanghai Fomar Laboratory Equipment), electric constant temperature water bath (Jiangsu Kedao), magnetic stirrer (Shanghai Meiyingpu), high-speed centrifuge (Guangzhou Jidi), vacuum pump (Beck, Germany), hot press (Shenzhen Chuangjia), ball mill (Henan Zhengkuang), freeze dryer (Shandong Deli); chemicals and reagents were purchased from Sigma-Aldrich.
[0022] Example 1: This example discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0023] The core material comprises the following raw materials in parts by weight: 47 parts of xylitol-aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of Cu-BTC-acylated soybean protein.
[0024] The clothing coating material adopts an innovative dual confinement structure and multiple molecular force network design. In terms of structure, aerogel carbon fiber is interwoven to form a honeycomb three-dimensional network structure with nano-scale pores, such as Figure 1 As shown, the octahedral lattice channels of Cu-BTC are interconnected, such as Figure 2 The multi-level pore structure from nanometer to micrometer is formed. This multi-level pore provides a nanometer-scale confined cavity and a micrometer-scale storage space for xylitol molecules, effectively restricting the xylitol molecules in a specific size space, thereby preventing them from flowing and leaking in a large range in a molten state.
[0025] In terms of the molecular force network, the material constructs a triple synergistic mechanism: first, the oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of the aerogel carbon fiber form a stable hydrogen bond network with the Cu²⁺ ions in the Cu-BTC metal center and the acyl (-CO-) and amino (-NH2) groups of the acylated soy protein; secondly, the Cu²⁺ in Cu-BTC forms a coordination bond (-O-Cu-O-) with the -OH groups of the xylitol molecules and the -COOH and -OH groups on the surface of the aerogel carbon fiber; finally, the polar groups on the surface of the aerogel carbon fiber form hydrogen bonds and electrostatic interactions with the shell material. This triple molecular force significantly enhances the binding force and compatibility of the core-shell interface. This triple molecular force significantly enhances the binding force and compatibility of the core-shell interface, preventing material separation. This triple molecular force significantly enhances the binding force and compatibility of the core-shell interface, preventing material separation.
[0026] To further improve the performance of the material, the acylated soy protein molecules are cross-linked through amide bonds (-CO-NH-) to form a mesh structure, and form a three-dimensional cross-linked network with the metal organic skeleton of Cu-BTC through coordination, providing excellent mechanical strength. At the same time, the flexible peptide chain of the acylated soy protein can absorb the volume stress during the phase change process, and with the support of the rigid skeleton of the aerogel carbon fiber, it can not only prevent the deformation of the microcapsules, but also achieve stress release and buffering, ensuring that the material maintains good temperature control effect and structural stability during use.
[0027] However, due to the difference in hydrophilicity between xylitol-aerogel carbon fiber and hydrophobicity of Cu-BTC-acylated soy protein, the interface bonding is not tight enough. CaCl2·6H2O can be used as an interface regulator to solve this problem. The Ca²⁺ ions form coordination bonds with the -OH groups of xylitol molecules, and at the same time establish coordination with the oxygen-containing functional groups (-COOH, -OH) on the surface of aerogel carbon fiber, and form coordination bonds with the carboxylic acid groups (-COOH) in Cu-BTC, forming a bridging network structure in the whole system, which effectively improves the mechanical strength and interface stability of the material.
[0028] The preparation method of the xylitol-aerogel carbon fiber comprises: S11. sieving xylitol through 60 mesh to obtain sieved xylitol, and vacuum drying the sieved xylitol at 60-70° C. for 8-10 hours to obtain pretreated xylitol; S12. Cut the aerogel carbon fiber into segments of 0.5 to 1 cm in length to obtain the cut aerogel carbon fiber, add the cut aerogel carbon fiber into a 3 to 5 mol / L HNO3 solution, and soak it at 70 to 80°C for 2 to 3 hours to obtain the soaked aerogel carbon fiber, continue to place the soaked aerogel carbon fiber in a 3 to 5 mol / L HNO3 solution for ultrasonic treatment for 30 to 45 minutes to obtain the ultrasonically treated aerogel carbon fiber, wash the ultrasonically treated aerogel carbon fiber with deionized water for 4 to 5 times to obtain aerogel carbon fiber washed with deionized water, wash the aerogel carbon fiber washed with deionized water with ethanol for 2 to 3 times to obtain aerogel carbon fiber washed with ethanol, and vacuum dry the ethanol-washed aerogel carbon fiber at 60 to 80°C for 12 to 24 hours to obtain the pretreated aerogel carbon fiber; S13. The pretreated xylitol is heated to 95-100° C. to obtain molten xylitol, the pretreated aerogel carbon fibers are slowly added to the molten xylitol, and mechanically stirred at 400-500 rpm for 30-40 min to obtain a mixed material, and the mixed material is ultrasonically treated at 60-70° C. for 30-40 min to obtain a mixed material after ultrasonic treatment; S14. The mixed material after ultrasound is placed in a vacuum box, evacuated to -0.08~-0.1MPa, and evacuated at 100~110°C for 2~3h to obtain a vacuum mixed material; S15. The vacuum mixed material is slowly cooled to room temperature at a cooling rate of 2 to 4 ° C / min to obtain a cooled mixed material, and the cooled mixed material is pressurized at 10 to 12 MPa using a hot press for 10 to 20 min to obtain a pressed mixed material; S16. The pressed mixed material is vacuum dried at 60-70° C. for 12-24 h to obtain xylitol-aerogel carbon fiber.
[0029] The preparation method of the Cu-BTC-acylated soybean protein comprises: S21. Weigh copper chloride hexahydrate and 1,3,5-benzenetricarboxylic acid, dissolve them in N,N-dimethylformamide to obtain a mixed solution, place the mixed solution in an oil bath at 70 to 80° C., and react at a constant temperature for 24 to 36 hours to obtain a mixed solution after the reaction; S22. The mixed solution after the reaction is cooled to room temperature to obtain a cooled mixed solution, the cooled mixed solution is vacuum filtered to obtain a precipitate, the precipitate is repeatedly washed with acetone for 3 to 4 times to obtain a washed precipitate, the washed precipitate is blown dry to obtain a blown-dried precipitate, and the blown-dried precipitate is vacuum dried at 60 to 70° C. for 12 to 24 hours to obtain Cu-BTC; S23. Weigh soy protein isolate and dissolve it in deionized water, and adjust the pH to 9 to 10 using 1 to 5 mol / L NaOH to obtain a soy protein isolate solution, and stir the soy protein isolate solution at room temperature for 1 to 2 hours to obtain a stirred soy protein isolate solution; S24. slowly adding acetic anhydride dropwise to the stirred soy protein isolate solution at 45-50° C. to obtain a mixed solution, stirring the mixed solution at a constant temperature for 3-4 hours to obtain a stirred mixed solution, adjusting the pH of the stirred mixed solution to 4.5-5 to obtain a pH-adjusted mixed solution, centrifuging the pH-adjusted mixed solution at 4000-6000 rpm for 15-20 minutes to obtain a precipitate, washing the precipitate with deionized water for 3-4 times to obtain a precipitate washed with deionized water, and freeze-drying the precipitate washed with deionized water for 24-36 hours to obtain an acylated soy protein; S25. dissolving the acylated soy protein in a phosphate buffer to obtain an acylated soy protein solution, ultrasonically dispersing the acylated soy protein solution for 15 to 20 minutes to obtain an acylated soy protein solution after ultrasonication, and allowing the acylated soy protein solution after ultrasonication to stand for swelling for 2 to 3 hours to obtain an acylated soy protein solution after standing; S26. Cu-BTC was added to phosphate buffer and ultrasonicated at 300-400W for 20-25min to obtain a Cu-BTC dispersion. The Cu-BTC dispersion was allowed to stand for 10-15min, and the supernatant was taken to obtain a Cu-BTC dispersion supernatant; S27. The supernatant of the Cu-BTC dispersion is added dropwise to the acylated soybean protein solution after standing at 2-3 mL / min by a constant flow pump to obtain a reaction solution, the reaction solution is ultrasonically dispersed for 30-45 min to obtain a reaction solution after ultrasonication, the reaction solution after ultrasonication is stirred at 400-500 rpm for 2-3 h to obtain a stirred reaction solution, the pH of the stirred reaction solution is adjusted to 7-8 to obtain a reaction solution with adjusted pH, the reaction solution with adjusted pH is stirred at room temperature for 1-2 h and then allowed to stand for 1-2 h to obtain a reaction solution after standing; S28. The reaction solution after standing is centrifuged at 8000-10000 rpm for 15-20 min to obtain a centrifuged reaction solution, the centrifuged reaction solution is washed with deionized water for 2-3 times and then with ethanol for 1-2 times to obtain a washed reaction solution, the washed reaction solution is vacuum dried at 60-70° C. for 8-12 h to obtain Cu-BTC-acylated soybean protein.
[0030] A method for preparing a coating material for clothing, applied to the coating material for clothing, comprises the following steps: S31. Grinding CaCl2·6H2O to 100-150 mesh to obtain ground CaCl2·6H2O; S32. Cut the aluminum foil into sheets of 2 to 3 mm in size to obtain cut aluminum foil, ultrasonically clean the cut aluminum foil with anhydrous ethanol for 5 to 10 minutes to obtain cleaned aluminum foil, and naturally dry the cleaned aluminum foil at room temperature to obtain pretreated aluminum foil.
[0031] S33. The ground CaCl2·6H2O and xylitol-aerogel carbon fiber were mixed in a constant temperature water bath at 25 to 29°C to obtain a first mixed material, and the pretreated aluminum foil was added to the first mixed material and gently stirred for 5 to 10 minutes to obtain a second mixed material; S34. The Cu-BTC-acylated soy protein was dissolved in anhydrous ethanol and ultrasonically treated for 10 to 15 minutes to obtain a Cu-BTC-acylated soy protein solution, and the second mixed material was added dropwise to the Cu-BTC-acylated soy protein solution at a rate of 5 to 10 mL / min to obtain a third mixed material, and the third mixed material was stirred at 200 to 300 rpm for 30 to 45 minutes to obtain a fourth mixed material; S35. Allow the fourth mixed material to stand for 2 to 3 hours to obtain the fourth mixed material after standing, centrifuge the fourth mixed material after standing at 3000 to 5000 rpm for 10 to 20 minutes to obtain the fourth mixed material after centrifugation, wash the fourth mixed material after centrifugation with deionized water for 3 to 4 times to obtain the washed fourth mixed material, and vacuum dry the washed fourth mixed material at 60 to 70° C. for 12 to 24 hours to obtain the clothing coating material.
[0032] Example 2: This example discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0033] The core material comprises the following raw materials in parts by weight: 50 parts of xylitol-aerogel carbon fiber, 40 parts of CaCl2·6H2O, and 10 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 20 parts of Cu-BTC-acylated soybean protein.
[0034] The preparation method of xylitol-aerogel carbon fiber and Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0035] Example 3: The example discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0036] The core material comprises the following raw materials in parts by weight: 40 parts of xylitol-aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 5 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 15 parts of Cu-BTC-acylated soybean protein.
[0037] The preparation method of xylitol-aerogel carbon fiber and Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0038] Example 4: The example discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0039] The core material comprises the following raw materials in parts by weight: 45 parts of xylitol-aerogel carbon fiber, 35 parts of CaCl2·6H2O, and 7.5 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 17.5 parts of Cu-BTC-acylated soybean protein.
[0040] The preparation method of xylitol-aerogel carbon fiber and Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0041] Control group 1: This embodiment differs from embodiment 1 in that it does not contain xylitol-aerogel carbon fiber.
[0042] This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure. The microcapsule includes a core material and a shell material. The core material is composed of CaCl2·6H2O and is provided with an aluminum foil barrier layer. The shell material is Cu-BTC-acylated soybean protein, which is used to wrap the core material and form a stable microcapsule structure.
[0043] The core material comprises the following raw materials in parts by weight: 30 parts of CaCl2·6H2O and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of Cu-BTC-acylated soybean protein.
[0044] The preparation method of the Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0045] Control group 2: This embodiment differs from embodiment 1 in that it does not contain CaCl2·6H2O.
[0046] This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0047] The core material comprises the following raw materials in parts by weight: 47 parts of xylitol-aerogel carbon fiber and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of Cu-BTC-acylated soybean protein.
[0048] The preparation method of xylitol-aerogel carbon fiber and Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0049] Control group 3: This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC, which is used to wrap the core material and form a stable microcapsule structure.
[0050] The core material includes the following raw materials by weight: 47 parts of xylitol-aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil; the shell material includes the following raw materials by weight: 18 parts of Cu-BTC.
[0051] The preparation methods of xylitol-aerogel carbon fiber and Cu-BTC in this embodiment are consistent with those in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0052] Control group 4: This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0053] The core material comprises the following raw materials in parts by weight: 47 parts of xylitol-aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of acylated soybean protein.
[0054] The preparation method of xylitol-aerogel carbon fiber and acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0055] Control group 5: This example discloses a coating material for clothing, wherein the core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer.
[0056] The core material comprises the following raw materials in parts by weight: 47 parts of xylitol-aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil.
[0057] The preparation method of the xylitol-aerogel carbon fiber of this embodiment is consistent with that of embodiment 1. The preparation method of a coating material for clothing of this embodiment is consistent with that of embodiment 1.
[0058] Control group 6: This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0059] The core material comprises the following raw materials in parts by weight: 47 parts of aerogel carbon fiber, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of Cu-BTC-acylated soybean protein.
[0060] The preparation methods of the aerogel carbon fiber and Cu-BTC-acylated soybean protein in this embodiment are consistent with those in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0061] Control group 7: This embodiment discloses a coating material for clothing, which is composed of a microcapsule structure, wherein the microcapsule includes a core material and a shell material; the core material is composed of xylitol and CaCl2·6H2O, and is provided with an aluminum foil barrier layer; the shell material is Cu-BTC-acylated soy protein, which is used to wrap the core material and form a stable microcapsule structure.
[0062] The core material comprises the following raw materials in parts by weight: 47 parts of xylitol, 30 parts of CaCl2·6H2O, and 6 parts of aluminum foil; the shell material comprises the following raw materials in parts by weight: 18 parts of Cu-BTC-acylated soybean protein.
[0063] The preparation method of xylitol and Cu-BTC-acylated soybean protein in this embodiment is consistent with that in Example 1. The preparation method of a coating material for clothing in this embodiment is consistent with that in Example 1.
[0064] Test verification: 1. Dynamic leakage rate test: The sample size is 10cm×10cm, the temperature cycle range is 15~40℃, and it is cycled 20 times. The initial weight and the weight after the cycle are weighed, and the weight loss rate is calculated.
[0065] 2. Static leakage test: The sample size is 10cm×10cm, the temperature is kept at 40℃ for 36h, the pressure is evenly loaded at 2kPa, and the leakage volume is measured.
[0066] 3. Washing cycle test: water temperature is 40℃, washing rate is 30min / time, dry naturally after each wash, weigh every 10 cycles, and calculate the weight change rate.
[0067] 4. Thermal stability: The temperature cycle range is 15~40℃, the cycle rate is 2h / time, and the cycle is repeated 2 times. The delamination index is calculated.
[0068] 5. Interface bonding strength test: sample size is 250 mm × 25 mm, tensile speed is 100 mm / min, test temperature is 25°C, and the maximum peeling force is recorded.
[0069] 6. Phase change temperature: The sample size is 2mm×2mm, the test temperature range is 0-50℃, and the phase change temperature range is marked.
[0070] Table 1 Performance test of clothing coating materials in the embodiment group and the control group
[0071] From the overall performance point of view, the four embodiment groups are significantly better than the control group, among which embodiment 1 has the best performance, with a dynamic leakage rate of only 0.5%, a static leakage of 0.2g / m², a weight change rate of -1.2% after washing cycle, a delamination index of 0.02, an interface bonding strength of 8.5N / cm, and a phase change temperature range of 15.5-33.8℃. The performance ranking is embodiment 1> embodiment 4> embodiment 3> embodiment 2, which is related to the ratio of materials. Embodiment 1 embodies the best ratio and achieves the optimal synergistic effect of multi-level pore structure, triple molecular force network and interface regulation.
[0072] The experimental data of the control group reflects the key role of each component: the performance of control group 1 (no xylitol-aerogel carbon fiber) and control group 5 (no shell material) is the worst, among which the dynamic leakage rate of control group 5 is as high as 4.2%, and the interface bonding strength is only 2.5N / cm, indicating that the complete structure of the microcapsule is crucial to the material performance. The interface bonding strength of control group 2 (no CaCl2·6H2O) dropped significantly to 3.8N / cm, confirming the key role of Ca²⁺ ions in interface regulation. The performance of control group 3 (only Cu-BTC as shell material) and control group 4 (only acylated soy protein as shell material) is between the embodiment group and other control groups, indicating that the composite reinforcement effect of Cu-BTC and acylated soy protein is better than that of a single component. The experimental data of control group 6 (no xylitol) and control group 7 (no aerogel carbon fiber) verified the importance of the synergistic system of xylitol-aerogel carbon fiber.
[0073] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A coating material for clothing, characterized in that: The microcapsule comprises a core material and a shell material; The core material is composed of xylitol-aerogel carbon fiber, CaCl2·6H2O, and is provided with an aluminum foil barrier layer; The shell material is Cu-BTC-acylated soybean protein, which is used to wrap the core material and form a stable microcapsule structure.
2. A coating material for clothing as claimed in claim 1, characterized in that: The core material comprises the following raw materials in parts by weight: 40-50 parts of xylitol-aerogel carbon fiber, 30-40 parts of CaCl2·6H2O, and 5-10 parts of aluminum foil; The shell material comprises the following raw materials in parts by weight: 15 to 20 parts of Cu-BTC-acylated soybean protein.
3. A coating material for clothing as claimed in claim 2, characterized in that: The preparation method of the xylitol-aerogel carbon fiber comprises: S11. sieving xylitol through 60 mesh to obtain sieved xylitol, and vacuum drying the sieved xylitol at 60-70° C. for 8-10 hours to obtain pretreated xylitol; S12. Cut the aerogel carbon fiber into segments of 0.5 to 1 cm in length to obtain the cut aerogel carbon fiber, add the cut aerogel carbon fiber into a 3 to 5 mol / L HNO3 solution, and soak it at 70 to 80°C for 2 to 3 hours to obtain the soaked aerogel carbon fiber, continue to place the soaked aerogel carbon fiber in a 3 to 5 mol / L HNO3 solution for ultrasonic treatment for 30 to 45 minutes to obtain the ultrasonically treated aerogel carbon fiber, wash the ultrasonically treated aerogel carbon fiber with deionized water for 4 to 5 times to obtain aerogel carbon fiber washed with deionized water, wash the aerogel carbon fiber washed with deionized water with ethanol for 2 to 3 times to obtain aerogel carbon fiber washed with ethanol, and vacuum dry the ethanol-washed aerogel carbon fiber at 60 to 80°C for 12 to 24 hours to obtain the pretreated aerogel carbon fiber; S13. The pretreated xylitol is heated to 95-100° C. to obtain molten xylitol, the pretreated aerogel carbon fibers are slowly added to the molten xylitol, and mechanically stirred at 400-500 rpm for 30-40 min to obtain a mixed material, and the mixed material is ultrasonically treated at 60-70° C. for 30-40 min to obtain a mixed material after ultrasonic treatment; S14. The mixed material after ultrasound is placed in a vacuum box, evacuated to -0.08~-0.1MPa, and evacuated at 100~110°C for 2~3h to obtain a vacuum mixed material; S15. The vacuum mixed material is slowly cooled to room temperature at a cooling rate of 2 to 4 ° C / min to obtain a cooled mixed material, and the cooled mixed material is pressurized at 10 to 12 MPa using a hot press for 10 to 20 min to obtain a pressed mixed material; S16. The pressed mixed material is vacuum dried at 60-70° C. for 12-24 h to obtain xylitol-aerogel carbon fiber.
4. A coating material for clothing as claimed in claim 2, characterized in that: The preparation method of the Cu-BTC-acylated soybean protein comprises: S21. Weigh copper chloride hexahydrate and 1,3,5-benzenetricarboxylic acid, dissolve them in N,N-dimethylformamide to obtain a mixed solution, place the mixed solution in an oil bath at 70 to 80° C., and react at a constant temperature for 24 to 36 hours to obtain a mixed solution after the reaction; S22. The mixed solution after the reaction is cooled to room temperature to obtain a cooled mixed solution, the cooled mixed solution is vacuum filtered to obtain a precipitate, the precipitate is repeatedly washed with acetone for 3 to 4 times to obtain a washed precipitate, the washed precipitate is blown dry to obtain a blown-dried precipitate, and the blown-dried precipitate is vacuum dried at 60 to 70° C. for 12 to 24 hours to obtain Cu-BTC; S23. Weigh soy protein isolate and dissolve it in deionized water, and adjust the pH to 9 to 10 using 1 to 5 mol / L NaOH to obtain a soy protein isolate solution, and stir the soy protein isolate solution at room temperature for 1 to 2 hours to obtain a stirred soy protein isolate solution; S24. slowly adding acetic anhydride dropwise to the stirred soy protein isolate solution at 45-50° C. to obtain a mixed solution, stirring the mixed solution at a constant temperature for 3-4 hours to obtain a stirred mixed solution, adjusting the pH of the stirred mixed solution to 4.5-5 to obtain a pH-adjusted mixed solution, centrifuging the pH-adjusted mixed solution at 4000-6000 rpm for 15-20 minutes to obtain a precipitate, washing the precipitate with deionized water for 3-4 times to obtain a precipitate washed with deionized water, and freeze-drying the precipitate washed with deionized water for 24-36 hours to obtain an acylated soy protein; S25. dissolving the acylated soy protein in a phosphate buffer to obtain an acylated soy protein solution, ultrasonically dispersing the acylated soy protein solution for 15 to 20 minutes to obtain an acylated soy protein solution after ultrasonication, and allowing the acylated soy protein solution after ultrasonication to stand for swelling for 2 to 3 hours to obtain an acylated soy protein solution after standing; S26. Cu-BTC was added to phosphate buffer and ultrasonicated at 300-400W for 20-25min to obtain a Cu-BTC dispersion. The Cu-BTC dispersion was allowed to stand for 10-15min, and the supernatant was taken to obtain a Cu-BTC dispersion supernatant; S27. The supernatant of the Cu-BTC dispersion is added dropwise to the acylated soybean protein solution after standing at 2-3 mL / min by a constant flow pump to obtain a reaction solution, the reaction solution is ultrasonically dispersed for 30-45 min to obtain a reaction solution after ultrasonication, the reaction solution after ultrasonication is stirred at 400-500 rpm for 2-3 h to obtain a stirred reaction solution, the pH of the stirred reaction solution is adjusted to 7-8 to obtain a reaction solution with adjusted pH, the reaction solution with adjusted pH is stirred at room temperature for 1-2 h and then allowed to stand for 1-2 h to obtain a reaction solution after standing; S28. The reaction solution after standing is centrifuged at 8000-10000 rpm for 15-20 min to obtain a centrifuged reaction solution, the centrifuged reaction solution is washed with deionized water for 2-3 times and then with ethanol for 1-2 times to obtain a washed reaction solution, the washed reaction solution is vacuum dried at 60-70° C. for 8-12 h to obtain Cu-BTC-acylated soybean protein.
5. A method for preparing a coating material for clothing, which is applied to prepare the coating material for clothing as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: S31. Grinding CaCl2·6H2O to 100-150 mesh to obtain ground CaCl2·6H2O; S32. The aluminum foil was cut into sheets of 2 to 3 mm in size to obtain a cut aluminum foil, the cut aluminum foil was ultrasonically cleaned with anhydrous ethanol for 5 to 10 min to obtain a cleaned aluminum foil, and the cleaned aluminum foil was naturally dried at room temperature to obtain a pretreated aluminum foil; S33. The ground CaCl2·6H2O and xylitol-aerogel carbon fiber were mixed in a constant temperature water bath at 25 to 29°C to obtain a first mixed material, and the pretreated aluminum foil was added to the first mixed material and gently stirred for 5 to 10 minutes to obtain a second mixed material; S34. The Cu-BTC-acylated soy protein was dissolved in anhydrous ethanol and ultrasonically treated for 10 to 15 minutes to obtain a Cu-BTC-acylated soy protein solution, and the second mixed material was added dropwise to the Cu-BTC-acylated soy protein solution at a rate of 5 to 10 mL / min to obtain a third mixed material, and the third mixed material was stirred at 200 to 300 rpm for 30 to 45 minutes to obtain a fourth mixed material; S35. Allow the fourth mixed material to stand for 2 to 3 hours to obtain the fourth mixed material after standing, centrifuge the fourth mixed material after standing at 3000 to 5000 rpm for 10 to 20 minutes to obtain the fourth mixed material after centrifugation, wash the fourth mixed material after centrifugation with deionized water for 3 to 4 times to obtain the washed fourth mixed material, and vacuum dry the washed fourth mixed material at 60 to 70° C. for 12 to 24 hours to obtain the clothing coating material.
Citation Information
Patent Citations
Color-changing sunscreen fabric and preparation method thereof
CN112779789A
Anti-digestion starch soybean protein compound and preparation method thereof
CN115624167A
Modification method of soybean protein concentrate
CN1689430A